A study of factors which determine the supply of pigs - O'Connor, R. (Statistical and Social Inquiry Society of Ireland, 1954)
In a free economy, where prices and production are not controlled, pig numbers move in characteristic cycles, each cycle averaging about four years in length. These pig cycles are the resultant of many physical and economic forces, and the whole pattern of production and prices has been given a generalised explanation which is referred to in the United States as the " Cobweb Theorem."
Read before the Society, 18 December 1954
Keywords: Cobweb model; Agriculture, Ireland; Pig supply, Ireland; 314.15